Identifying and synthesizing components of perinatal mental health peer support – a systematic review - Hölzle, Laura; Schöch, Philipp; Hörtnagl, Christine; Buchheim, Anna; Lampe, Astrid; Zechmeister-Koss, Ingrid; Paul, Jean Lillian (Frontiers in Psychiatry, 2024)
Background: Becoming a parent, while often perceived as a joyous event, can also be a vulnerable life transition, with approximately one in five mothers experiencing perinatal mental illness. Peer support is recommended for its preventive and therapeutic benefits. However, relevant program components of perinatal mental health peer support remain to be identified.Objectives: This review aims to (1) identify peer support programs in perinatal mental health through existing reviews and to (2) synthesize the components of these programs.Methods: A systematic literature review guided by PRISMA was conducted searching four databases, supplemented by hand searches. The Template for Intervention Description and Replication (TIDieR) checklist facilitated the systematic extraction and synthesis of program components. Results: Eleven peer support programs were identified from three reviews, largely conducted in English-speaking countries. The identified reviews highlight the benefits of peer support in perinatal mental health. Key components of individual programs were contextual background, materials, provider training and support, delivery modes and locations, and evaluation. Sharing lived experience and providing flexible support were central to all programs.Conclusion: Aspects of flexibility, authenticity and the challenges of program evaluation in peer support must be considered. Findings can now inform future planning and implementation efforts of peer support programs in periantal mental health.